Numerical Study on the Effects of Regional Groundwater Flow on the Contaminant Migration through an Inactive Supply Well as a Preferential Flow Pathway - Xu Li; Shilin Su; Qiang Guo; Haitao Zhang; Qi Zhu; Hamza Jakada (Geofluids)
Preferential flow pathways connect upstream and downstream channels in abandoned mines or seasonally pumping areas. The inactive supply well facilitates contaminant migration between aquifers leading to water quality challenges; it is important to note that the impacts of regional groundwater flow on contaminant migration through pumping wells have not been well elucidated in literature. In the study, we developed a numerical model describing contaminant migration through an inactive supply well that is pumped seasonally influenced by the regional groundwater flow field. The model was developed using the finite-element COMSOL Multiphysics software to estimate the potential threats to water quality. Major findings showed that a larger regional groundwater velocity results in lower concentration of contaminant. In addition, during pumping, a smaller recovery ratio inside the wellbore facilitates the deterioration of water quality in the deep aquifer. Furthermore increasing pumping frequency can effectively prevent contamination and improve the water quality in the deep aquifer. Similarly, higher pumping rate leads to a larger capture zone, which can significantly improve the water quality in the deep aquifer. The general conclusion is that the regional groundwater flow has a negative impact on the quality of groundwater extracted by seasonally pumping well.